PEMANFAATAN TEPUNG BEKATUL TERHADAP SIFAT SENSORI DAN KIMIA PRODUK COOKIES - Nofia Sofianti; Dwi Novri Supriatiningrum; Sutrisno Adi Prayitno (Ghidza Media Jurnal, 2021)
Rice bran is the outer layer of rice that is released during milling and contains nutrients that is fiber, carbohydrates, protein and vitamin B complex which can be used as additional ingredients in making cookies. This study aims to determine the effect of rice bran substitution on the sensory and chemical properties of cookies products. The research design used was a completely randomized design (CRD) with 4 replications, Organoleptic test was analyzed by Friedman test and chemical test was analyzed by ANOVA and followed by LSD test. Organoleptic test results show that there is an effect of rice bran substitution on sensory properties including color, aroma, taste and texture of rice bran cookies, indicating that H0 is rejected and H1 is accepted. The best results were found in substitution (30%) and the lowest was in substitution (50%). The results of chemical test analysis showed that the highest protein content was in the treatment (50%) bran of 8.19 g, the highest carbohydrate content in the treatment (100%) of flour was 78.70 g, the highest level of vitamin B1 showed treatment (50%) of bran flour was 1.35 mg, while in the fiber test the highest value was obtained in the treatment (50%) of bran flour of 11.25 g. The best treatment for rice bran cookies is low carbohydrate value, high in protein, vitamin B1 and fiber.